Acting Of Proposal Program For Growing Skills Of Reasoning Thinking For Sample Of Students Of University Of Baghdad – college Of Physical Education - Kailan, Bidaa (Journal of Physical Education, 2010)
The reasoning thinking is not only for acquiring knowledge but also include personality of life for individual that need reasoning thinking to solve problems . The reasoning thinking has appositive role in learning firstly . The student has self – discoing in under standing and solving problem is aright way secondly the teacher has reasoning way in detecting the wrong of students , so the most trainings and growing of skills for reasoning thinking are needed . The important of this study represents under standing how to from these skills . The sample of this study has two groups ; controlled and experimental group . each group contains (18) students . The study contains skills of reasoning thinking and test of intelligence and program of growing reasoning thinking . The researcher know the differences between pre – test for each group